BDNF serum levels and cognitive improvement in drug-naive first episode patients with schizophrenia: A prospective 12-week longitudinal study. (December 2020) - Wu, Zhi Wei; Shi, Hui; Chen, Da Chun; Chen, Song; Xiu, Mei Hong; Zhang, Xiang Yang
Highlights: 354 DNFE patients and 152 controls were recruited. 211 patients were treated with risperidone monotherapy for 12 weeks. BDNF levels were decreased in patients and slightly increased after risperidone treatment. Baseline serum BDNF levels were associated with improvement of delayed memory. Baseline BDNF was a prognostic factor for the improvement of cognitive function. Abstract: Abnormal brain-derived neurotrophic factor (BDNF) levels are involved in cognitive decline in patients with schizophrenia. The role of atypical antipsychotic risperidone in improving cognitive function remains unclear. The study aimed to investigate the effect of risperidone monotherapy on cognitive impairment in drug-naïve first-episode (DNFE) patients with schizophrenia and whether BDNF levels were correlated to the improvement of cognition. 354 DNFE patients and 152 healthy controls were recruited, and we compared their serum BDNF levels and cognition shown on the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). High and low BDNF subgroups were defined by median split. Then, 211 patients were treated with risperidone monotherapy for 12 weeks, and their serum BDNF levels and cognition were measured again after treatment. DNFE patients had poorer cognitive functions and lower BDNF levels compared to controls. Lower BDNF levels were correlated with delayed memory in DNFE patients with high baseline BDNF levels. After 12 weeks of treatment, risperidone significantly improved immediate memory, delayed memory and RBANS total scores and BDNF levels were slightly increased. In patients with low-BDNF, BDNF levels were significantly increased after risperidone treatment, while in patients with high-BDNF, BDNF levels were significantly decreased. In addition, baseline BDNF levels were associated with improvement of delayed memory and were a prognostic factor for the improvement of the delayed memory and RBANS total score in patients with high-BDNF. Our result suggests risperidone treatment can partially improve certain domains of the cognitive impairment and baseline BDNF levels are related to cognitive response to risperidone in DNFE patients with schizophrenia.